The nonlinear analysis of an innovative slit reinforced concrete water tower in seismic regions. (1st March 2017) - Gurkalo, F.; Du, Y.G.; Poutos, K.; Jimenez-Bescos, C.
Highlights: Feasibility of the silt in water towers. Non-linear performance of water tower assembled with silt in a server earthquake. Mitigation of seismic damages of water tower. Stress redistribution of water tower in an earthquake. Abstract: Water towers are widely used in our society as one of water distribution facilities within water network systems. In the event of a severe earthquake, however, a single plastic hinge that occurs in a water tower could cause its total collapse before nonlinear resources of the rest of the tower remains fully utilised. This research presents an innovative technique for the assembly of a water tower using the slits in its reinforced concrete shaft for the purpose of mitigating the seismic response. Slit shafts were designed to have four slits at 90° intervals along the full height of the shafts. The shaft parts were connected to each other at the bottom, top and every five meters with coupling beams. The slit width was used as a variable in this study which varied between 50 mm and 2000 mm. The nonlinear seismic performance of the proposed slit towers was analysed by means of a finite element approach with respect to soil types defined in Eurocode 8 and seismic behaviour were compared to the solid water tower. A detailed observation of the compression and tension stress distributions with respect to the slit width was performed. The obtained analytical results revealed that slit width in the reinforced concrete tower affect the failure mode and stiffness of a water tower significantly. With an appropriate design, the conversion of a solid water tower into a slit tower can significantly increase its ductility under seismic action without significantly compromising its bearing capacity. The results showed that contours of tension and compression stress intensity in shafts, which could lead to a failure of water towers, highly depended on the slit width. In the solid water tower, the stress concentration dominated at the base of the shaft, however in the narrow slit water towers the stresses were equally distributed along the height of the shafts. Also, the stresses were mostly concentrated at the top of the shafts in the wide slit water towers. Conclusively, the results provided useful information regarding the compression stress distribution along the slit shafts in the water towers which can be used in obtaining an optimum slit shaft design for different soil types.